Leaf temperature and photosynthetic performance in chickpea - Pinheiro, C (2012)
The responses of photosynthetic rate and leaf conductance to leaf temperature were evaluated in two contrasting chickpea genotypes (Elixir and FLIP03-46C) grown under field conditions (Elvas, Portugal). Photosynthetic performance was assayed with leaf temperatures ranging from 24ºC to 40º C under controlled VPD. Technical constraints and physiological implications are discussed.